2023
DOI: 10.1101/2023.09.12.557322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective advantage of mutant stem cells in clonal hematopoiesis occurs by attenuating the deleterious effects of inflammation and aging

Niels Asger Jakobsen,
Sven Turkalj,
Andy G. X. Zeng
et al.

Abstract: Clonal hematopoiesis (CH) arises when hematopoietic stem cells (HSC) acquire mutations in genes, includingDNMT3AandTET2, conferring a competitive advantage through a mechanism that remains unclear. To gain insight into how CH mutations enable gradual clonal expansion, we used single-cell multi-omics with high-fidelity genotyping on CH bone marrow samples. Most of the selective advantage of mutant cells occurs within HSCs.DNMT3AandTET2-mutant clones expand further in early progenitors, whileTET2mutations accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 120 publications
3
11
0
Order By: Relevance
“…6I, and Table S13). Notably, downregulation of inflammatory genes IL1R1 and ID2 within CH MUT HSC2/HSC-iM was found, in line with observed downregulation of TNFα via NFkB signaling within this population (72). These results are similar to those from the in vivo inflammation-recovery model wherein molecular changes following inflammatory treatment occurred predominantly within the HSC-iM population (Fig.…”
Section: Identification Of Xenograft-derived Hsc-im Signatures In Hum...supporting
confidence: 85%
See 4 more Smart Citations
“…6I, and Table S13). Notably, downregulation of inflammatory genes IL1R1 and ID2 within CH MUT HSC2/HSC-iM was found, in line with observed downregulation of TNFα via NFkB signaling within this population (72). These results are similar to those from the in vivo inflammation-recovery model wherein molecular changes following inflammatory treatment occurred predominantly within the HSC-iM population (Fig.…”
Section: Identification Of Xenograft-derived Hsc-im Signatures In Hum...supporting
confidence: 85%
“…By establishing an inflammation-recovery xenotransplantation model able to recapitulate HSC states found in aging and CH, we have identified clues towards answering these important questions. Critically, the HSC-iM subset identified from our xenograft model is remarkably similar, at a molecular level, to an HSC subset found in adult BM from our separate CH study (72). We found that DNMT3A and TET2 mutations have both cell-autonomous and non-cellautonomous effects on HSCs from CH donors.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations